2021
DOI: 10.1021/acs.macromol.0c02567
|View full text |Cite
|
Sign up to set email alerts
|

High-Electric-Field-Induced Hierarchical Structure Change of Poly(vinylidene fluoride) as Studied by the Simultaneous Time-Resolved WAXD/SAXS/FTIR Measurements and Computer Simulations

Abstract: A high electric field was applied cyclically to poly(vinylidene fluoride) films, during which the simultaneous and time-resolved measurements of the two-dimensional wideangle X-ray diffraction (WAXD), small-angle X-ray scattering (SAXS), and transmission-type Fourier transform infrared (FTIR) spectra were performed using a synchrotron X-ray radiation system. The inversion of the CF 2 dipole moments caused by the alternate change of the electric field vector direction was detected to occur around ±80−100 MV/m a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 57 publications
(120 reference statements)
4
24
0
Order By: Relevance
“…Thus, as a result 1209 cm −1 absorption band does not appear in IR spectra of δ -phase. 36 This observation is consistent with FTIR spectra of PVDF nanoparticles processed via electrospray. Additionally, the FTIR spectra (Fig.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Thus, as a result 1209 cm −1 absorption band does not appear in IR spectra of δ -phase. 36 This observation is consistent with FTIR spectra of PVDF nanoparticles processed via electrospray. Additionally, the FTIR spectra (Fig.…”
supporting
confidence: 86%
“…The fourier transform infrared spectroscopy (FTIR) study of the nanoparticles (Fig. S3 (marked as δ ), supplementary material) shows the IR absorption bands of δ -PVDF as reported by K. Tashiro et al 36 . The vibrational bands at 1182 cm −1 and 1209 cm −1 are one of the conclusive way to identify the δ -phase through FTIR.…”
mentioning
confidence: 56%
“…[ 7 ] Large‐scale transformation from α‐phase to β‐phase is induced by thermal and UV‐annealing, [ 8 ] mechanical deformation, [ 9 ] and electric field poling. [ 10 ] Very recently, Ding et al. demonstrated that nanoannealing of PVDF films could also be induced by gold nanoparticle‐assisted plasmonic heating under irradiation of continuous waver laser, which substantially facilitates the α‐ to β‐phase transformation.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Large-scale transformation from α-phase to β-phase is induced by thermal and UV-annealing, [8] mechanical deformation, [9] and electric field poling. [10] Very recently, Ding et al demonstrated that nanoannealing of PVDF films could also be induced by gold nanoparticle-assisted plasmonic heating under irradiation of continuous waver laser, which substantially facilitates the αto β-phase transformation. [11] With different conformations (trans-gauche-trans-gauche′ [TGTG′] for α-phase and all-trans [TTTT] for β-phase), Multiplexing physical dimensions to realize multidimensional storage in a single material has been a goal to increase storage density and data security.…”
mentioning
confidence: 99%
“…In order to trace the structural change of PVDF films in the electric field from the wide hierarchical structure levels, the present authors challenged to simultaneously measure two-dimensional WAXD patterns, the small-angle X-ray scattering (SAXS) patterns, and the transmission-type IR spectra in the process of stepwise change of electric field strength in the range of 0 to ±400 MV/m by using the synchrotron X-ray radiation system combined with a miniature FTIR spectrometer . The samples used there were the commercially available biaxially oriented PVDF films composed of the crystal forms α and β.…”
Section: Introductionmentioning
confidence: 99%